Organizing the Meatpacking Industry in the United States - Storch, Randi (Labour / Le Travail, 1998)
The article reviews and comments on Rick Halpern's "Down on the Killing Floor: Black and White Workers in Chicago's Packinghouses, 1904-54" (1997) and "Unionizing the Jungles: Labor and Community in the Twentieth-Century Meatpacking Industry" (1997) edited by Shelton Stromquist and Marvin Bergman.